The resistance of Eimeria spp. to toltrazuril in black grouse (Lyrurus tetrix) kept in an aviary. (10th July 2018) - Sokół, Rajmund; Gałęcki, Remigiusz
ABSTRACT: The black grouse is a critically endangered species in Europe. Aviary breeding and re-introduction programs have contributed to the reinstatement of black grouse populations. Parasitic diseases can influence the species' behavior, choice of habitats, and survival rates. Protozoa of the genus Eimeria are the most prevalent parasites in black grouse. The aim of this study was to evaluate the effectiveness of toltrazuril (TOL) against Eimeria spp. in black grouse kept in an aviary. Eimeria spp. oocysts (mean OPG for all birds = 7, 047.84; SD = 5, 625.05) were detected in feces samples in a routine parasitological examination. Parasitic infections were treated with toltrazuril Baycox 2.5% (Bayer, Leverkusen, Germany) at 1 ml/1 l H2 O administered per os with drinking water twice a day for 2 d, 12 h/24 h. High oocysts counts persisted upon the second parasitic examination. Therefore, the birds were divided into 3 groups in 3 existing aviaries. Toltrazuril was administered according to the same protocol, and its uptake with drinking water was monitored. A parasitological examination conducted 5 d later revealed the presence of parasites, and the TOL dose was increased to 3 ml/1 l H2 O. When oocysts were detected in a successive exam, the TOL dose was further increased to 5 ml/1 l H2 O. The increase in TOL dose did not eliminate parasites, therefore, the treatment was discontinued. The fecal egg count reduction test (FECRT) revealed that 1 ml of TOL reduced fecal oocysts counts (OPG) by 0.02%, the second application of the same TOL dose reduced OPG by 0%, 3 ml of TOL reduced OPG by 0%, and 5 ml of TOL reduced OPG by 65.7%. The applied doses of TOL did not induce significant differences in the fecal oocysts counts of any of the identified species of coccidia. The results indicate that the coccidia species infecting black grouse have natural resistance to TOL.